The Possibility of Using Green Hydrogen Solutions in a Concrete Production Case Study: An Analysis of Energy and Cost Perspectives - Serafini, D (Springer Nature, 2025)
Concrete is the second most consumed substance in the world, after water. According to the World Cement and Concrete Association, around 14 billion m3 of concrete are consumed annually. Unfortunately, its production has a significant environmental impact, ranking third in greenhouse gas (GHG) emissions and accounting for almost 8% of total emissions in 2023, according to the IEA. Of the sector’s total emissions, 70% result from the chemical reaction during the burning of cement in large kilns, while the remaining emissions come from electricity and fossil fuel consumption. This study assesses the feasibility of using electricity and green hydrogen in concrete production, focusing on a company in southern Chile. Three scenarios are compared: a wind power plant that supplies energy and produces hydrogen as a reserve; a green power purchase agreement (PPA) that supplies energy and produces hydrogen as a reserve; and the direct purchase of green hydrogen from an external company. The analysis revealed the levelized cost of hydrogen (LCOH) to be 7.96 [USD/kg] for the wind plant and 13.38 [USD/kg] for the PPA. The levelized cost of energy (LCOE) was 0.69 [USD/kWh] for the wind plant and 1.24 [USD/kWh] for the PPA. The purchase of green hydrogen did not provide sufficient data for viability, but significant cost reductions are projected from 2030. While current costs are high, optimizing green hydrogen technologies could make their future implementation viable, contributing to the decarbonization of the concrete industry. In addition to providing practical data on LCOH and LCOE, the study allows for a more accurate understanding of current economic challenges and future projections regarding hydrogen, and its main contribution is that it can help companies make strategic decisions regarding investments in green technologies. On the other hand, the research highlights the importance of green hydrogen as a sustainable alternative for sectors that are difficult to decarbonize and also addresses a regional case study. © The Author(s), under exclusive license to Springer Nature Switzerland AG 2025.